The influence of mouth opening on pharyngeal pressure loss and its underlying mechanism: A computational fluid dynamic analysis - Hu, Bin; Yin, Guoping; Fu, Song; Zhang, Baoshou; Shang, Yan; Zhang, Yuhuan; Ye, Jingying (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: During inspiration, mechanical energy generated from respiratory muscle produces a negative pressure gradient to fulfill enough pulmonary ventilation. The pressure loss, a surrogate for energy loss, is considered as the portion of negative pressure without converting into the kinetic energy of airflow. Mouth opening (MO) during sleep is a common symptom in patients with obstructive sleep apnoea-hypopnea syndrome (OSAHS). This study aimed to evaluate the effects of MO on pharyngeal pressure loss using computational fluid dynamics (CFD) simulation. Methods: A total of 4 subjects who were morphologically distinct in the pharyngeal characteristics based on Friedman tongue position (FTP) grades were selected. Upper airway computed tomography (CT) scan was performed under two conditions: mouth closing (MC) and MO, in order to reconstruct the upper airway models. CFD was used to simulate the flow on the two different occasions: MC and MO. Results: The pharyngeal jet was the typical aerodynamic feature and its formation and development were different from MC to MO in subjects with different FTP grades. For FTP I with MC, a pharyngeal jet gradually formed with proximity to the velopharyngeal minimum area plane (planeAmin). Downstream the planeAmin, the jet impingement on the pharyngeal wall resulted in the frictional loss associated with wall shear stress (WSS). A rapid luminal expansion led to flow separation and large recirculation region, corresponding to the interior flow loss. They all contributed to the pharyngeal total pressure loss. While for FTP I with MO, the improved velopharyngeal constriction led to smoother flow and a lower total pressure loss. For FTP IV, the narrower the planeAmin after MO, the stronger the jet formation and its impingement on the pharyngeal wall, predicting a higher frictional loss resulted from higher WSS. Besides, a longer length of the MO-associated constant constrictive segment was another important morphological factor promoting frictional loss. Conclusion: For certain OSAHS patients with higher FTP grade, MO-related stronger jet formation, more jet breakdown and stronger jet flow separation might contribute to the increased pharyngeal pressure loss. It might require compensation from more inspiratory negative static pressure that would potentially increase the severity of OSAHS.